Production of polysaccharides from white mushrooms (pleurotus florida) by submerged culture fermentation (scf) - Fazlin, Masra (2014)
P.florida is commonly available edible mushroom among different types of oyster mushrooms of the genus Pleurotus. The bioactive compound contain in the P.florida (polysaccharides and protein) have benefit to health include immunomodulatory, anti-cancer, and hypocholesterolemic effect. The objective of this research is to study the production of polysaccharides and biomass from white mushrooms (P. florida) by submerged culture fermentation (SCF) and determination of protein content by using Kjeldahl method. The effect of harvest time on the production of mycelial biomass, exopolysaccharides (EPS) and protein by P.florida was investigated in research. The optimal culture condition was 20 g/L glucose, 4 g/L yeast extract, 0.46 g/L KH2PO4, 1 g/L K2HPO4, and 0.5 g/L MgSO4 7 H2O at temperature 28oC and pH 8. The modes of reactor operation used in this cultivation of mushroom are shake flask and air lift bioreactor and Somogyi-Nelson reagent, Phenol-Sulphuric reagent and 4% Phenol reagent were used during the sample analysis. In this present study, the result implies that the highest biomass, polysaccharides and protein yield production change with the time of cultivation. This indicated that the maximum production of production day in producing biomass was at days 15 (2.464 g/L). However, the production polysaccharides and protein indicates the highest productivity on the same day (days 12) with 8.42 g/L and 28.69 % respectively. It was found that productivity in airlift bioreactor much higher than the productivity in the shake flask. Thus it can be concluded that that harvest time selection is very important factor to obtain maximal fungal production. This may due to the gentle agitation and aeration hydraulic in airlift bioreactor leads to the productivity of mycelia biomass, exopolysaccharides and protein more efficient than in shake flask